Genetic optimization of GRNN for pattern recognition without feature extraction - Polat, Oevuenc; Yildirim, Tuelay (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
This paper describes an approach for pattern recognition using genetic algorithm and general regression neural network (GRNN). The designed system can be used for both 3D object recognition from 2D poses of the object and handwritten digit recognition applications. The system does not require any preprocessing and feature extraction stage before the recognition. In GRNN, placement of centers has significant effect on the performance of the network. The centers and widths of the hidden layer neuron basis functions are coded in a chromosome and these two critical parameters are determined by the optimization using genetic algorithms. Experimental results show that the optimized GRNN provides higher recognition ability compared with that of unoptimized GRNN. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: genetic algorithm; general regression neural networks; pattern recognition; Computer Science; Engineering; Operations Research & Management Science